OVO E-Wallet as a Platform of Digital Payment in Indonesia: An Empirical Analysis - wiwik widiyanti; Vina Islami; Rani -; Syahrir -; Rosento - (Universitas Bina Sarana Informatika, 2020)
Abstract. Nowadays, payment systems in the digital era use more electronic money than physical money; one of the famous ones is OVO e-wallet. OVO has supported in some various merchandises, so that people can easily download and use it. Moreover, the trust of the community is very important that OVO continues to be used in every online transaction in almost every places and vendors. The purpose of this study is to study the factors that influence the use of OVO by its consumers. The location of the research in Depok, West Java, Indonesia. The number of respondents is 123 persons; who were surveyed by online using the convenience sampling methods. This type of research is a quantitative research with explanatory analysis. The analysis technique uses validity, reliability, and hypothesis testing by using the AMOS application as a data processing tool. The results of this study indicate that the perceived ease of use, trust, and benefits significantly influence the combination of OVO use. Based on the results of the research, the research proves that OVO can convince the users of the data in the OVO application that confidentiality is guaranteed so that OVO can be trusted.